Pengaruh Kualitas Pelayanan, Harga dan Lokasi Terhadap Switching Intention Pada Cafe Cerita Kopi Xotus Telang Bangkalan - ghufron, iqbal; setiyarini, triana (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
Coffee Shop is the place that provides various type of coffee and other nonalcoholic drinks in a relax atmosphere, a comfortable places and equipped with music, either through audio or live music, a distinctive interior design, friendly service and some of them provides wireless internet connection or wifi. The purpose of this study is: 1) To test the factor of Service Quality affecting Switching Intention 2) To analyze the factor of Price affecting Switching Intention. 3) To test the location affecting Switching Intention. This studying use a quantitative research method is a research method base on the philosophy of positivism, used to study a certain population or sample, data collection use research instruments, in this study using the Cochran formula obtained a sample of 124 respondents. The conclusion in this study is. 1. From the results of the hypothesis test that has been conducted, it shows that service quality has a significant effect on switching intention (X). 2. Price has a significant effect on switching intention. This can be seen from the results of P values, which are 0.000 0.05. Therefore, these results indicate that price has an effect on switching intention (X2). 3. Location has a significant effect on switching intention. This can be seen from the results of P values, which are 0.000 0.05. Therefore, these results indicate that location has an effect on switching intention (X3).